‘Stokvels’ as an alternative housing finance mechanism: a case study of ‘Masakhe’ ladies in Gugulethu - Motupa, Dikeledi (University of the Witwatersrand, Johannesburg, 2024)
Stokvels have been a longstanding financial mechanism in South Africa, historically providing savings and credit avenues, particularly for marginalised communities excluded from formal banking systems. Despite improved access to banking for black South Africans, the formal mortgage market remains largely inaccessible to the poor owing to constraints in the affordable housing market. With government housing initiatives constrained by overwhelming demand, many continue to lack housing assistance. This study explores stokvels as an alternative housing finance mechanism, focusing on the Masakhe Ladies stokvel group in Gugulethu through qualitative case study research approach. The study employs semi-structured interviews and evaluation research to explore how stokvels, as an alternative housing finance mechanism, offer a way for low-income households to gain access to adequate housing. A theoretical framework is constructed from literature on stokvels, adequate housing, self-help housing, enablement, inequality livelihoods and poverty, and enablement. Findings indicate that stokvels, through collaboration with government, private and governmental entities, can facilitate access to adequate housing. While acknowledging that this is a single case study the recommendation emphasises focusing efforts not on universal applicability but on adapting the collaborative model to meet the specific needs of diverse communities, ensuring tailored and effective outcomes.
A research report submitted in fulfillment of the requirements for the Master of Built Environment in Housing, In the Faculty of Engineering and the Built Environment , School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Stokvel; Financial house; Community-base savings; SDG-8: Decent work and economic growth